Electrochemical Performance and Preliminary Post-Mortem Analysis of a Solid Oxide Cell Stack with 20, 000 h of Operation. Issue 2 (1st January 2018) - Fang, Qingping; Frey, Carolin E.; Menzler, Norbert H.; Blum, Ludger
Abstract : A long-term test with a two-layer solid oxide cell stack was carried out for more than 20, 000 hours. The stack was mainly characterized in a furnace environment in electrolysis mode, with 50% humidification of H2 at 800°C. The endothermic operation was carried out with a current density of −0.5 Acm −2 and steam conversion rate of 50%. Electrolysis at lower temperatures (i.e., 700°C and 750°C) and fuel cell operation (with 0.5 Acm −2 and fuel utilization of 50%) at 800°C were also carried out (<2000 h each) for comparison. The voltage and area specific resistance degradation rates were ∼0.6%/kh and 8.2%/kh after ∼18, 460 hours of operation. In total, the stack was operated above 700°C for more than 20, 000 hours. Impedance measurement and analysis showed that the increase of ohmic resistance was the main degradation phenomenon, while electrode polarizations were kept nearly constant before a severe burning took place in one layer. Ni-depletion in fuel electrodes was confirmed during post-mortem analysis, which was assumed to be the major degradation mechanism observed. The stack performance and degradation analysis under different working conditions, as well as the results of preliminary post-mortem analysis will be presented.